Identifying Drought-Tolerant Impatiens Genotypes by Using Water Stress Treatment - Shintiavira, Herni; Purba, Ardian Elonard; Kartikaningrum, Suskandari; Koseki, Atsushi (Universitas Sebelas Maret, 2023)
The drought-tolerant Impatiens genotypes are known for their resistance to limited or stressed water. The study aimed to identify drought-tolerance of Impatiens clones. The experiment used a split-plot design replicated three times, with the water stress treatment as the main plot and Impatiens clones as subplots. The main plot consists of 100% and 60% of field capacity. The subplots consist of five Impatiens clones, 17.12; 12; 33.3; 40 B and Impatiens cv of Impala Agrihorti as a control. The results showed that 60% field capacity decreased morphological and physiological traits. Still, the drought-tolerant clones were less affected by the stress and produced more flowers than the others. The most drought-tolerant Impatiens was clone 12. The mechanism of drought tolerance Impatiens was by stomatal closure when the humidity in the growing medium was decreasing. The stomata closure did not significantly reduce the fresh and dry weight in drought-tolerant plants, but it affected the delay in flower initiation. The plant accumulated assimilate for plant height and diameter growth but is not sufficient for generative initiation. They assimilate in the vegetative phase and can be used as sources for flower formation, which show no significant decrease in the number of flowers. The study implies that the drought-tolerant Impatiens clones can be used as genotype sources for drought-tolerant or can be released as new varieties of Impatiens for landscape plants with the superiority in having drought tolerant.